INTERFERENSI BAHASA INDONESIA DALAM BAHASA ARAB: KASUS PADA KESALAHAN BERBAHASA SISWA KELAS X MAN 1 SRAGEN - Amatullah, Muna Nabila; Aziza, Lady Farah (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2020)
In the process of learningnew language, language learner will experience language contact and then cause language interference. This study aims to determine (1) Forms and type of Indonesian interference found in Arabic language among class X MAN 1 Sragen; (2) factors causing language interference; and (3) solution to reduce language interference. The study used a qualitative research design. The data were collected through listening and recording method. Data were analyzed using Hubung Banding technique. The results of the study revealed that (1) language interference occurs in 214 cases contained phonological, morphological, and syntactic interference; (2) the causes of interference are bilingualism, differences on language structure between L1and L2, and lack of vocabulary; (3) solution to reduce language interference are teacher may speak Arabic pronunciation clearly, correcting learner errors immediately, doing imla’ lesson and classroom activities that help learners improve their language skill.